miRNA: The nemesis of gastric cancer (Review) - XU, XIAOHUI (D.A. Spandidos, 2013)
microRNAs (miRNAs) are a group of small non-coding RNAs that are ~22 (18 to 25) nucleotides (nt) long and have been associated with a variety of diseases, including cancer. Increasing evidence indicates that miRNAs are essential in the development, diagnosis, treatment and prognosis of a variety of tumors. The utility of miRNAs as biomarkers for diagnosis and of target molecules for the treatment of cancers is increasingly being recognized. With the discovery of circulating miRNAs, a non-invasive approach for the diagnosis and treatment of cancer has been identified. This review summarizes the role of miRNAs in the development of different tumors, as well as a variety of other biological events. Moreover, this review focuses on analyzing the function and mechanism of gastric cancer-related miRNAs and investigates the importance of circulating miRNAs in gastric cancer, as well as their origin. Finally, this review lists a number of the problems that must be solved prior to miRNAs being used as reliable non-invasive tools for the diagnosis, treatment and prognosis of gastric cancer.